PENAMPILAN BEBERAPA GALUR DAN VARIETAS JAGUNG DI LAHAN KERING ( The Performance of Corn Lines and Varieties in Dryland ) - Syafri Edi (Bioplantae, 2013)
Research of agronomic characteristic performance from some promising  lines  and varieties of corn in dry land was held in Desa Sebapo, Mestong  Kabupaten Muaro Jambi Provinsi Jambi. The purpose of this study was to determine the agronomic characteristics of some promising lines and varieties of corn in dry land. The research design was Randomized Block design  with nine treatments , Lines 08 x Tester 01,  Lines  010 x Tester 01, Lines 011 x Tester 01, Galur 02 x Tester 01, Lines 010 x Tester 02 and  Lines 01 x Tester 02, and 2 corn hybrid  C-7 and  Bisi-2 and 1 composite corn varieties  Sukmaraga. and  all treatment repeat 3 times. Variables measured were plant height  at harvest, cob height, cob diameter, cob length, number of rows per cob, number of seeds per row, yield of seed, 100 seed weight and yield per hectare of dry loose. The results showed that Lines 010 x Tester 02 gives the best result 6.20 t/ha. Key words: Maize, agronomic characteristics, dry land